Підвищення термотолерантності промислових спиртових дріжджів шляхом дерепресії генів синтезу трегалози - Лужецький, Т.Б.; Семкін, М.В.; Кшановська, Б.В.; Дмитрук, К.В.; Сибірний, А.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of this work is the elevation of the thermotolerance and improvement the efficiency of high temperature alcoholic fermentation of yeast S. cerevisiae by overexpression of the genes TPS1 and TPS2. Methods. For overexpression of trehalose-6-phosphate synthase and trehalose-6-phosphate phosphatase the vector for multicopy integration was constructed, where ORFs of TPS1 and TPS2 genes were placed under the control of strong constitutive promoter ADH1. The resulting vector was linearized and used for transformation of S. cerevisiae industrial strains. Results. Recombinant strains overexpressing genes for trehalose synthesis possessed increased intracellular concentration of trehalose. Thermotolerance and efficiency of high temperature alcoholic fermentation of the constructed strains were increased. Conclusions. Recombinant strains with higher intracellular trehalose concentration produce 17% more ethanol during fermentation at 42°C. Constructed strains are promising for industrial implementation.